Management of chronic hand and foot eczema. An Australia/New Zealand Clinical narrative. (10th August 2020) - Rademaker, Marius; Armour, Katherine; Baker, Christopher; Foley, Peter; Gebauer, Kurt; Gupta, Monisha; Marshman, Gillian; O'Connor, Alicia; Rubel, Diana; Sullivan, John; Wong, Li‐Chuen
Abstract: Chronic hand/foot eczemas are common, but treatment is often challenging, with widespread dissatisfaction over current available options. Detailed history is important, particularly with regard to potential exposure to irritants and allergens. Patch testing should be regarded as a standard investigation. Individual treatment outcomes and targets, including systemic therapy, should be discussed early with patients, restoring function being the primary goal, with clearing the skin a secondary outcome. Each new treatment, where appropriate, should be considered additive or overlapping to any previous therapy. Management extends beyond mere pharmacological or physical treatment, and requires an encompassing approach including removal or avoidance of causative factors, behavioural changes and social support. To date, there is little evidence to guide sequences or combinations of therapies. Moderately symptomatic patients (e.g. DLQI ≥ 10) should be started on a potent/super‐potent topical corticosteroid applied once or twice per day for 4 weeks, with tapering to twice weekly application. If response is inadequate, consider phototherapy, and then a 12‐week trial of a retinoid (alitretinoin or acitretin). Second line systemic treatments include methotrexate, ciclosporin and azathioprine. For patients presenting with severe symptomatic disease (DLQI ≥ 15), consider predniso(lo)ne 0.5–1.0 mg/kg/day (or ciclosporin 3 – 5 mg/kg/day) for 4–6 weeks with tapering, and then treating as for moderate disease as above. In non‐responders, botulinum toxin and/or iontophoresis, if associated with hyperhidrosis, may sometimes help. Some patients only respond to long‐term systemic corticosteroids. The data on sequencing of newer agents, such as dupilumab or JAK inhibitors, are immature.